Quality Questions of Clinch Join - Jónás, Szabolcs; Tisza, Miklós (International Journal of Engineering and Management Sciences, 2018)
This article deals with the quality of the clinch joints. Due to the volume of the production there is a need for the inspection of the joints and the monitoring of the joining process. Different producers give solutions for the inspection and monitoring and these solutions will be introduce through 1-1 example their importance.